The Relationship Between Organizational Intelligence And Organizational Agility In Hospitals Of Mashhad University Of Medical Sciences - Mohammad Reza Zabihi; Seyed Saeed Tabatabaee; Mohammad Reza Ghamari; Mohammad Hanif Asadi (Tehran University of Medical Sciences, 2015)
Background and Aim: Due to the changing environment of hospitals and the necessity of providing services for patients in the shortest possible time and at an acceptable quality and cost, it seems to be necessary to utilize the maximum intellectual capacity of the organization to enhance agility in hospitals. The aim of this study is, in fact, to investigate the relationship between organizational intelligence (and its components according to the Albrecht model) and organizational agility in hospitals of Mashhad University of Medical Sciences. Materials and Methods: This descriptive study was conducted in 2013 on 408 hospital employees seleced through stratified sampling method. To collect data on organizational intelligence, the Albrekht standardized questionnaire was used and to gather data on organizational agility, a questionnaire designed based on Goldman model was employed. For data analysis and hypothesis testing, the SPSS software version16, Pearson correlation, t-test, Anova, and regression techniques were applied. Results: The results of the study showed that there was a significant relationship between agility in hospitals and organizational intelligence ( components : Appetite for change, heart, knowledge deployment, performance pressure, strategic vision, shared fate, and alignment and congruence). The determinants of agility were mainly strategic vision, performance pressure, and a lignment and congruence. Conclusion: The results of the study showed that dynamic strategic planning in hospitals and developing educational programs of organizational intelligence aiming at employees' and managers' awareness could lead to an increase in the agility level of hospitals and provision of effective services for patients.